Comparing Determinants of Effective Collaboration in a Comprehensive Crime Reduction Initiative. Issue 3 (2nd July 2016) - Gebo, Erika; Bond, Brenda J.
ABSTRACT: Increasingly there is a call from policy makers for communities to work collaboratively to ameliorate social problems; yet, collaborating is arguably one of the most difficult tasks of partnerships. Conceptual frameworks for effective collaboration have recently been developed and need empirical testing. Effective collaboration determinants are explored in this study of a comprehensive crime reduction initiative. Comparative case study methodology is used to examine the presence of these determinants in three arenas: context, structure, and function. Sites were most similar in structure; differences were most pronounced in function. Translating these results in this initiative and across other community partnerships is discussed.